2021
DOI: 10.1007/s11255-021-03056-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gut microbiota in hemodialysis patients with sarcopenia

Abstract: Purpose Maintenance hemodialysis (MHD) patients are at high risk of sarcopenia. Gut microbiota affects host metabolic and may act in the occurrence of sarcopenia importantly. This study aimed to study the characterization of the gut microbiota in MHD patients with sarcopenia, and to further reveal the complex pathophysiology of sarcopenia in MHD patients. Methods Fecal samples and clinical data were collected from 30 MHD patients with sarcopenia, and 30 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Until now, only a few studies have examined the association between gut microbiota and sarcopenia in human beings. 16 , 17 , 18 , 19 , 23 Four studies have shown that several bacterial genera differed between sarcopenia cases and controls 16 , 17 , 18 , 19 ; however, all these studies used 16S rRNA amplicon sequencing, which limited their ability to identify closely related species. Only one study found significant differences in the composition and functionality of the gut microbiome between sarcopenic patients and non‐sarcopenic controls using shotgun metagenomic sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Until now, only a few studies have examined the association between gut microbiota and sarcopenia in human beings. 16 , 17 , 18 , 19 , 23 Four studies have shown that several bacterial genera differed between sarcopenia cases and controls 16 , 17 , 18 , 19 ; however, all these studies used 16S rRNA amplicon sequencing, which limited their ability to identify closely related species. Only one study found significant differences in the composition and functionality of the gut microbiome between sarcopenic patients and non‐sarcopenic controls using shotgun metagenomic sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Although animal studies have shown promise, there are complexities and limitations inherent in translating reductionist animal models to complex human diseases. Until now, only a few studies have examined the association between gut microbiota and sarcopenia in human beings 16–19,23 . Four studies have shown that several bacterial genera differed between sarcopenia cases and controls 16–19 ; however, all these studies used 16S rRNA amplicon sequencing, which limited their ability to identify closely related species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last 2 years, several observational studies have demonstrated relevant associations between gut microbial parameters and presence of sarcopenia or alterations of muscle function [14 ▪▪ ,15 ▪▪ ,16–22]. They are summarized in Table 1.…”
Section: The Gut Microbiota and Trajectories Of Ageingmentioning
confidence: 99%